LAND-WATER ISSUES IN TURKISTAN IN THE “TARJIMAN” NEWSPAPER (Scientific journal of the Fergana State University, 2023)
the oppression of the Russian Empire. The article also used materials from the first Turkestan publications, “Taraqqi”, “Tujjor” This article is based on the materials of the Jadid leader Ismail Gasprinsky and his newspaper “Tarjimon”, the colonial policy of land and water relations in Turkestan during and “Shuhrat”. The facts and information in the article have been studied based on the principle of historicity. The research process used microhistory, quantitative, systematic, content analysis and problem-chronological methods.